Peran Literasi Keuangan dalam Memoderasi Pengaruh Inklusi Keuangan dan Digital Payment terhadap Kinerja UMKM - Dewa Ayu Sanisca Tryana Putri; I Gusti Ayu Agung Pradnya Dewi (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study examines the impact of financial inclusion and the use of digital payment on MSME performance, with financial literacy serving as a moderating variable. The research adopts a quantitative approach, employing purposive sampling to select 150 MSME owners as respondents. Data were collected through questionnaires measured using a five-point Likert scale. The data analysis was conducted using Moderated Regression Analysis (MRA) with the assistance of SPSS software. The findings indicate that financial inclusion and digital payment usage have a significant positive effect on MSME performance. Furthermore, financial literacy is proven to strengthen the relationship between financial inclusion and MSME performance, while it weakens the effect of digital payment usage on performance. These results suggest that MSME owners’ financial management capabilities play a crucial role in determining the effectiveness of financial services and digital payment technologies. This study provides important implications for MSME development, particularly highlighting the need to enhance financial literacy so that business owners can optimize the use of financial services and digital technologies to support business performance.